2022
DOI: 10.1186/s44147-022-00165-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cement stabilised residual soil on macro- and micro-scale for road construction

Abstract: Lateritic soil is a kind of residual soil widespread in tropical countries. This soil usually possesses acceptable engineering properties to be laid under the construction projects. However, it needs treatment for transportation infrastructure such as railway and road subgrade and embankment, particularly when it is in fine-grained form. Thus, cement, one of the very common stabiliser agents in soil stabilisation, was selected to study its influence on lateritic soil at macro- and micro-levels. In order to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The cement hydration and pozzolanic reactions produce calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), leading to strength gains in calcium-based stabilized geomaterials [ 100 , 101 ], particularly cement-stabilized composites [ 102 , 103 ]. A previous study’s findings showed that cement hydration products fully adhere to the surface of carbon nanomaterials [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cement hydration and pozzolanic reactions produce calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), leading to strength gains in calcium-based stabilized geomaterials [ 100 , 101 ], particularly cement-stabilized composites [ 102 , 103 ]. A previous study’s findings showed that cement hydration products fully adhere to the surface of carbon nanomaterials [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this objective, substantial financial resources are allocated by authorities for the construction and maintenance of road networks. Nonetheless, challenges persist in the form of road pavement defects and transportation infrastructure failures, including issues such as rutting, cracking, reduced durability, slope instability, and excessive permanent strain accumulation [2][3][4]. These failures can be attributed to various factors, such as environmental conditions, groundwater levels, and excessive loading [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%